2020
DOI: 10.1002/jeq2.20023
|View full text |Cite
|
Sign up to set email alerts
|

Optimum rates of surface‐applied coal char decreased soil ammonia volatilization loss

Abstract: Fertilizer N losses from agricultural systems have economic and environmental implications. Soil amendment with high C materials, such as coal char, may mitigate N losses. Char, a coal combustion residue, obtained from a sugar factory in Scottsbluff, NE, contained 29% C by weight. A 30‐d laboratory study was conducted to evaluate the effects of char addition on N losses via nitrous oxide (N2O) emission, ammonia (NH3) volatilization, and nitrate (NO3–N) leaching from fertilized loam and sandy loam soils. Char w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 64 publications
1
35
1
Order By: Relevance
“…This explains why there was lower daily NH 3 volatilization in the treatment C1N1 compared to C0N1 only on Day 6. This observation is supported by previous research that demonstrates an importance of soil pH in retaining or releasing soil NH 4 /NH 3 (Fan et al., 1993; Panday et al., 2020; Sherlock et al., 1994). When comparing between char and no char fertilized treatments, a reduction in NH 3 loss with char treatment also coincided with a trend for higher residual NH 4 –N with that treatment than no char from Day 4 to 8.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This explains why there was lower daily NH 3 volatilization in the treatment C1N1 compared to C0N1 only on Day 6. This observation is supported by previous research that demonstrates an importance of soil pH in retaining or releasing soil NH 4 /NH 3 (Fan et al., 1993; Panday et al., 2020; Sherlock et al., 1994). When comparing between char and no char fertilized treatments, a reduction in NH 3 loss with char treatment also coincided with a trend for higher residual NH 4 –N with that treatment than no char from Day 4 to 8.…”
Section: Discussionsupporting
confidence: 86%
“…Clay minerals can fix total applied N in soil, which can reduce the pool of available N for NH 3 volatilization (Pelster et al., 2018). The reduction in NH 3 volatilization in char added fertilized treatment by 15.3% compared to no char treatment was due to increased N sorption due to higher surface area and CEC associated with char compared to soil (Panday et al., 2020). This observation agreed with previous research that documented a reduction in NH 3 volatilization with char addition to the fertilized treatment (Wang & Alva, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Panday et al. (2020) reported that char applied at 6.6 and 9.9 Mg C ha −1 in sandy loam and at 6.6, 9.9, and 13.1 Mg C ha −1 in loam soil reduced ammonia volatilization compared with no char treatment in their incubation experiment. This greater N retention in char‐applied soil should have resulted into yield gain in char treatments.…”
Section: Discussionmentioning
confidence: 98%
“…In this experiment, we used coal combustion residue, referred to as char, which was a partially combusted sub‐bituminous coal char sourced from the Western Sugar Cooperative sugar beet processing facility (Panday et al., 2020). Coal is used at the facility to fire traveling grate stoker furnaces to produce steam during the sugar extraction process.…”
Section: Methodsmentioning
confidence: 99%